The Flavonoid constituents of Pyrus Communis L. cv. Bon Chretien with special reference to discoloration during canning - Nortje, B. K.(Barend Kruger) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1964.